Therapeutic options following second-line platinum-based chemotherapy in patients with recurrent ovarian cancer: Comparison of active surveillance and maintenance treatment. (November 2020) - Ray-Coquard, Isabelle; Mirza, Mansoor Raza; Pignata, Sandro; Walther, Axel; Romero, Ignacio; du Bois, Andreas
Highlights: Active surveillance does not delay progression of recurrent ovarian cancer (rOC). Maintenance treatments for rOC (bevacizumab, PARP inhibitors) are underutilized. Maintenance treatment significantly extends PFS vs control for patients with rOC. PARP inhibitors improve overall survival in patients with BRCA-mutant rOC. All eligible patients with rOC should be offered targeted maintenance treatment. Abstract: Most women with advanced ovarian cancer respond to initial treatment, consisting of surgical resection and ≈6 cycles of platinum-based chemotherapy. However, disease recurrence occurs in most patients, and subsequent therapies become necessary. Historically, close monitoring following treatment (active surveillance) was the only available option, as continued maintenance chemotherapy treatment led to increased toxicity without providing any meaningful clinical benefit. Recently, targeted therapy with the angiogenesis inhibitor bevacizumab and the poly(ADP-ribose) polymerase (PARP) inhibitors olaparib, niraparib, and rucaparib have demonstrated significant clinical benefits as maintenance treatment for recurrent disease. Despite consensus guidelines recommending their use, maintenance treatments are currently underutilized. Here, we review evidence from pivotal clinical trials of approved second-line maintenance treatments demonstrating efficacy in terms of progression-free survival and postprogression efficacy outcomes for patients with recurrent ovarian cancer. Adverse events frequently associated with bevacizumab include hypertension, proteinuria, and non-central nervous system bleeding, whereas PARP inhibitors are associated with nausea, vomiting, fatigue, and anemia. Patient-centered outcomes analyses show that PARP inhibitors provide significant benefits to patient health status, even when accounting for the toxicities associated with treatment. Many factors influence the selection of second-line maintenance treatment for patients with recurrent ovarian cancer, including the maintenance treatment received in the first-line setting. Overall, targeted maintenance treatment represents a new standard of care for patients with ovarian cancer, and we recommend that maintenance treatment should be offered to all eligible patients with recurrent ovarian cancer.